SADE’S ALCOVE : LABORATORY OF DEBAUCHERY - Venus Brasileira Couy (Travessias, 2012)
Through rhetoric and language that makes drain secretions from the mouth or some other orifice of libertines or victims, in Philosophy in the Alcove, Sade opens the way for the debate, the divergence of ideas, dialogue, argumentation and philosophizing. The libertine-philosopher often implies the tone of the thinker of the Enlightenment. The essay focuses on the boudoir, prime location of the libertine scene, which is located between the lounge and bedroom, an area of ​​transition between the public and more private space of all. Thus, Sade carries the philosophical discussion to the environment of. The alcove, this room exclusively female, symbolizes the place of union of philosophy and body.